Effect of high‐pressure treatment on the quality of prepared chicken breast. (18th September 2020) - Dong, Kai; Luo, Xin; Liu, Lan; An, Fengping; Tang, Daobang; Fu, Lingyun; Teng, Hui; Huang, Qun
Summary: In this study, the effect of high‐pressure processing (HPP) on the physico‐chemical properties and microstructure of prepared chicken breast meat products was investigated. The result showed that the pH and TBARS values of the prepared chicken breast gradually increased, while the total volatile basic nitrogen value constantly decreased with the increase of pressure (0.1–500 MPa). In addition, the colour attributes ( L * and a * values) and texture indexes (hardness and chewiness) significantly improved as the pressure increased. The results of low‐field nuclear magnetic resonance demonstrated that the peak area of immobilised water (T22 ) first enhanced and then declined with the increase of pressure, reaching the maximum value at 200 MPa. Moreover, the integrity of microstructure and protein secondary structure of prepared chicken breast were also disrupted. These findings could serve as a theoretical basis for a better application of HPP in prepared chicken breast meat products. Abstract : The prepared chicken breast is a kind of new and nutritious food with the chicken breast as raw material and processed by vacuum rolling. The physicochemical properties and microstructure of chicken breast meat treated with high‐pressure can be improved obviously. It provides the foundation for the development of chicken breast in food processing.